PECULIARITIES OF APPLYING HOUSE ARREST AND MEANS OF INDIVIDUAL CONTROL DURING MARTIAL LAW - Litvinova, Iryna; Shylova, Kristina (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is to analyze the possibilities and limitations of applying house arrest and individual control measures under martial law with a view to ensuring effective control over citizens who may pose potential security threats. The author examines the legal, ethical and practical aspects of applying these measures, taking into account the peculiarities of martial law and the need for a balanced approach between ensuring the security of society and protecting the rights and freedoms of citizens. The research methods include analysis of legislation on the use of house arrest and individual control measures under martial law, as well as study of case law and experience of other countries in this area. In addition, the methods of sociological surveys and analysis of expert opinions are used to determine the public’s attitude to the use of such measures in the context of a military conflict. The results of the study indicate the need for careful regulation of the use of house arrest and individual control measures during martial law in order to ensure a balanced approach between public security and protection of citizens’ rights. The identified problems and needs will contribute to the further development of the legal and institutional mechanism of control in the context of martial law. Discussion: the article highlights the need to develop more specific criteria for the use of house arrest and individual control during martial law, taking into account the specifics of the conflict and ensuring the protection of citizens’ rights. The author also discusses possible ways to improve the effectiveness of control over persons under such restrictions in order to prevent cases of abuse of power or violation of their rights.